Intraoperative sedation and postoperative analgesic effects of bupivacaine-dexmedetomidine mixture compared to bupivacaine alone in upper extremity bone surgeries: A randomized comparative study in Vietnam - Nhung Thi Cam Tran; Khanh Hoang Pham; Thang Nguyen; Dao Huynh Tran; Hung Xuan Tong; Chung Van Nguyen (Faculty of Pharmacy, Mahidol University, 2022)
We aimed to compare intraoperative sedation and postoperative analgesic effects of brachial plexus block using bupivacaine-dexmedetomidine mixture (BD) versus bupivacaine alone (B) in upper extremity bone surgeries. We conducted a randomized comparative study at Can Tho City, Vietnam. We recruited patients aged 15 to 75 years, ASA (American Society of Anesthesiology) I-III grade, indicating bone surgeries of arm or forearm with supraclavicular brachial plexus block by ultrasound guidance. One hundred eight included patients were randomly divided into two groups: the BD group (54 patients) received a 30 ml mixture of 0.25% bupivacaine and 100 mcg dexmedetomidine, and the B group (54 patients) received 30 ml of 0.25% bupivacaine. The BD group had a sedative OAA/S score (Observer Assessment of Alertness/Sedation Scale) of level 4, accounting for 87% more than group B 37%, and an OAA/S score of level 3 in the BD group with 5 cases (9.3%) compared with 9 cases (16.7%) in group B, statistically significant difference with p<0.05. The onset and duration of sedative time in group BD was 9.8±3.5 and 92.7±34.1 minutes. The mean of postoperative analgesic time was 970.5±309.5 minutes in group BD statistically significantly longer than group B's with 552.7±231.2 minutes (p<0.001). In conclusion, a mixture of bupivacaine-dexmedetomidine in brachial plexus block for arm and forearm surgical fractures had greater sedative and postoperative analgesic effects than that of bupivacaine alone.